Treatment of acidic water from Bekok River using open limestone channel - Aris, Azmi (IWA Publishing, 2007)
Bekok River is one of the raw water resources for Batu Pahat treatment plants which supply treated water for domestic, institutional, commercial and industrial use. Due to soil characteristics and agricultural activities in the catchment area, pH of lower than 5.5 is common to the river, particularly in the stretch where the water intake point is located. However, at times, Bekok River registered low pH of less than 3.5 and hence caused problems to the treatment plants. The cost to neutralise the water increased and treatment scheduling became more complicated. A preliminary laboratory scale study has been conducted to determine the viability of using an open limestone channel as an in-situ pH treatment in the river. Two sets of experiments using synthetic and actual raw waters with various sizes and amount of limestone were carried out. Results indicate the viability of the process. Depending on the initial pH and acidity of the raw water, the pH can rise to 6.0 within 30 minutes of contact time. The amount and size of limestone was found to play an important role in minimising the contact time.